Exploratory Study Of Obstacles In Safety Culture Development In The Construction Industry: A Grounded Theory Approach - Kulchartchai , Oulawan; Hadikusumo, Bonaventura H.W. (Penerbit Universiti Sains Malaysia, 2010)
The aim of this paper is to analyse the obstacles that prevent the development of a safety culture in Thailand‟s large construction industry from various managerial points of view. Qualitative research methods were used by performing a series of semi-structured interviews of eight case studies selected from six prominent construction firms to investigate the obstacles they face. Glaser‟s keyword coding from Grounded Theory (GT) was used to reduce the information load after the interviews. Our findings revealed that the factors influencing the successful development of a safety culture in the construction industry are the workers, the characteristics of construction, the subcontractors, the supervisors, and external factors. Based on the frequency analysis, the main obstacles in developing a safety culture result from problems related to the workers themselves. The three most frequently discussed problems are unskilled workers, unsafe worker habits, and high worker turnover. Our results also suggest that managers should encourage engagement from their workers to optimise the successful implementation of safety programs and their long-term improvement.